Design and experimental characterization of hydraulically actuated revolute joint based on multimaterial additive manufacturing - Pfeil, Antoine; Siegfarth, Marius; Pusch, Tim Philipp; Barbé, Laurent; Geiskopf, Francois; Renaud, Pierre (Journal of mechanical design, 2022)
Design of fluidic actuators remain challenging in specific contexts such as the medical field, when solutions have for instance to be compatible with the stringent requirements of magnetic resonance imaging. In this article, an innovative design of hydraulically actuated revolute joint is introduced. The design originality is linked to the use of multimaterial additive manufacturing for its production. Hydraulic actuation and polymer manufacturing are selected to have compatibility with the medical context. A design taking advantage of the process capabilities is proposed. The proposed component associates a large stroke compliant revolute joint and miniature pistons. An helical rack-and-pinion mechanism is integrated to the compliant joint to control the joint rotation. A specific gear geometry is elaborated to minimize the joint size. It is experimentally characterized in terms of range of motion, stiffness, and available torque to discuss the suitability of the component as a fluidic actuator. The component offers an interesting compactness and range of motion and the process is shown to be adequate for the design of functional systems.